Sustainability of a digital health intervention within Pakistan’s remote health system: learning from implementation research - Saleem Sayani; Momina Muzammil; Malika Saba; Fayaz Roomi; Mirajuddin Miraj; Zeenat Sulaiman (Journal of the Pakistan Medical Association)
Pakistan faces significant challenges in attaining the Sustainable Development Goals for maternal and child health by the 2030 target. Separate vertical programmes, governance challenges due to paper-based systems, and limited availability of data contribute to the health system’s suboptimal functioning. An innovative mHealth tool, Hayat, was introduced in remote areas of Pakistan to digitalise record-keeping by frontline workers, provide evidence-based awareness content for dissemination, and track performance through transparency enhanced by geographical information system tracking. There has been a limited translation of mHealth evidence into policy change globally. Hayat is one of the few donor-funded programmes, and strengthens the health system in Pakistan. It secured matching funding from the government to sustain operations and for scale-up. The current paper was planned to describe the intrinsic and extrinsic factors that led to the intervention’s adoption by the government, including the technological and programmatic approaches, challenges and mitigation strategies,